Federal Prosecution Service Renewal: Year in review: Renewing the FPS Commitment to Canadians August 2002 - (:unkn) unknown (My University, 2016)
The Federal Prosecution Service (FPS) Year in Review reports on the progress of renewal to FPS staff, Justice Canada colleagues, and partners in Canada’s criminal justice system. It demonstrates that constructive change is happening and that the FPS has come a long way in managing the complexities of change, by focusingon strategic priorities and seeking solutions by working in partnership with others.Although considerable progress has been made, it is also recognized that Renewal is an ongoing process.